No future without transition: a critique of liberal peace - Fourlas, George N. (International journal of transitional justice, 2015)
In this article, I argue that developed liberal states require a movement away from a politics of control and toward techniques of reconciliation that are too often reserved for transitional societies. I first critique the liberal peace model on the grounds that it lacks an internal mechanism for maintaining peace and stability. I then discuss liberal praxis through an analysis of the US prison system, to demonstrate that a society can be nominally liberal and still fail to meet its own standards. Using the US as a cautionary tale, I suggest that by responding to social conflict through force, the liberal system increases instability by fragmenting communities and maintaining an individualistic order that is combative, thus leaving peace and justice as dormant possibilities. After critiquing liberal theory and practice, I discuss a corrective alternative, an ethics and politics of reconciliation that draws on restorative and transitional responses to instability.